2005
DOI: 10.1007/s11095-004-9010-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Downregulation of Hepatic Cytochrome P450 Expression and Activity in a Rat Model of Inflammatory Pain

Abstract: These early biochemical and metabolic modifications may have pharmacokinetic and pharmacodynamic consequences when hepatically cleared drugs are administered to FCA-treated rats, especially within the first 24-72 h post-FCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Our results clearly demonstrate that arthritis induced by FCA does not alter the pharmacokinetic behaviors of diclofenac in rats. However, some reports have shown that acute inflammation may alter the pharmacokinetics of NSAIDs [24,25] . This discrepancy may come from the oscillations of activities of CYP enzymes over period of inflammation and drugs [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly demonstrate that arthritis induced by FCA does not alter the pharmacokinetic behaviors of diclofenac in rats. However, some reports have shown that acute inflammation may alter the pharmacokinetics of NSAIDs [24,25] . This discrepancy may come from the oscillations of activities of CYP enzymes over period of inflammation and drugs [25] .…”
Section: Discussionmentioning
confidence: 99%
“…1, B and C). A confounding factor with the use of CFA is that it induces inflammation, which decreases the expression of P450s, and therefore it can inhibit drug bioactivation (Monshouwer et al, 1996;Projean et al, 2005). In the initial experiments, we treated animals with INH during the immunization schedule; later, we waited for 4 weeks from the last immunization with hepatic protein in IFA before starting INH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In rat lipopolysaccharide-or Freund's complete adjuvant-induced inflammation, mRNA levels of CYP3A2 were reduced by 60% of the control, and those of CYP3A1 were reduced by approximately 85% of the control (Sewer and Morgan, 1998;Projean et al, 2005). It seems that down-regulation of hepatic CYP3A genes is a common feature of inflammatory states, and it can also be applied to our PAN-induced nephrosis model.…”
Section: Increased Absorption Of Cyclosporine a In A Nephrosis Modelmentioning
confidence: 90%